Expressão dos genes TFF1 e TFF2 em adenocarcinoma gástrico - HAGE, Pedro Antônio Mufarrej (Universidade Federal do Pará, 2014)
Gastric cancer remains a serious public health problem with high morbidity and mortality. Generally, the diagnoses occur in advanced disease when the available therapeutic options have limited effectiveness. Despite advances in the understanding of carcinogenesis of gastric adenocarcinoma, particularly on genetic and epigenetic mechanisms involved, the clinical aplicabilitadade such knowledge remains limited. In order to identify potential biomarkers in gastric cancer, we conducted a study using microarray comparing gene expression in gastric adenocarcinomas and paired samples of non- neoplastic gastric mucosa. Preliminary, the results showed significant differences in expression of 53 genes. Among these, the TFF1 and TFF2 genes were selected for validation of expression by real-time PCR in 78 additional samples. Expression of TFF1 and TFF2 were significantly reduced in samples of gastric adenocarcinoma when you compare the paired non-neoplastic tissues (p<0.05). Additionally, the TFF2 gene expression was significantly lower in the intestinal subtype than in the diffuse subtype. The expression of the two genes showed a strong correlation, the similar pattern of expression suggests that TFF1 and TFF2 may have common regulatory elements. This hypothesis is enhanced due to the small physical distances between them. The results suggest the involvement of TFF1 and TFF2 in gastric carcinogenesis and demonstrate the potential for clinical use of these genes as biomarkers and potential therapeutic targets in gastric adenocarcinoma.